A panel of ten microsatellite loci for the Chagas disease vector Rhodnius prolixus (Hemiptera: Reduviidae) - Fitzpatrick, S.; Watts, P.C.; Feliciangeli, M.D.; Miles, M.A.; Kemp, Stephen J. (Elsevier, 2009)
Rhodnius prolixus is the main vector of Chagas disease in Venezuela, where it is found colonising rural housing consisting of unplastered adobe walls with palm and/or metal roofs. Vector control failure in Venezuela may be due to the invasion of houses by silvatic populations of R. prolixus found in palms. As part of a study to determine if domestic and silvatic populations of R. prolixus are isolated, thus clarifying the role of silvatic populations in maintaining house infestations, we constructed three partial genomic microsatellite libraries. A panel of ten dinucleotide polymorphic microsatellite markers was selected for genotyping. Allele numbers per locus ranged from three to twelve, with observed and expected heterozygosity ranging from 0.26 to 0.55 and 0.32 to 0.66. The microsatellite markers presented here will contribute to the control of Chagas disease in Venezuela and Colombia through the provision of population information that may allow the design of improved control strategies.